Impatience and grades : delay-discount rates correlate negatively with college GPA - Kris N. Kirby; Gordon C. Winston; Mariana Santiesteban (Williams College, Williams Project on the Economics of Higher Education (WPEHE), 2002)
Because the rewards of academic performance in college are often delayed, the delay-discounting model of impulsiveness (Ainslie, 1975) predicts that academic performance should tend to decrease as people place less weight on future outcomes. To test this hypothesis, we estimated (hyperbolic) discount rates for real delayed monetary rewards (10 to 20) using second-price auction procedures with 247 undergraduates at two liberal arts colleges. College GPA was reliably correlated with discount rates, r = -.19 (p = .003), and remained reliable after partialling out SAT scores. The results add to the external validity of the discounting model of impulsiveness, and point to a possible contributor to academic performance of interest in the study of higher education.
Keywords: 330; Bildungsverhalten; Studium; Bildungsertrag; Abzinsung; Schätzung; USA